Algoritmy klasifikace paketů - Machala, Jiří (Vysoké učení technické v Brně. Fakulta informačních technologií, 2012)
Hlavním cílem této práce je interpretace a implementace algoritmu HyperCuts. Zabývá se však i problémem klasifikace paketů obecně - shrnuje teoretické základy klasifikace a popisuje nejznámější klasifikační metody. Zaměřuje se především na vyhodnocení HyperCuts v porovnání s algoritmem HiCuts a analyzuje přínos optimalizací popsaných v odoborných článcích. Navrhuje nový způsob snížení počtu přístupů do paměti kombinací HyperCuts a HiCuts na jednom klasifikátoru.

The main aim of this work is interpretation and implementation of HyperCuts algorithm. It also covers the problematic of packet classification in general - it sums up the basic classification theory and introduces well-known classification methods. It concentrates mostly on evaluation of HyperCuts in comparison to HiCuts algorithm and analyses the assets of optimizations described in professional literature. It proposes a new way to limit the number of memory accesses by combining HyperCuts and HiCuts for single classifier.
Packet Classification Algorithms
Keywords: klasifikace paketů; HyperCuts; HiCuts; implementace; porovnání; packet classification; HyperCuts; HiCuts; implementation; comparison